Epidemiologic study of young soccer player`s injuries in U12 to U20 - Tourny, C.; Sangnier, S.; Cotte, T.; Langlois, R.; Coquart, J. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: The aim of this study was an epidemiological report of the injuries to young soccer players from pretraining centres (12 to 15 years: U12-U15) and training centres (16 to 20 years: U16-U20).